ANALISIS YURIDIS TERHADAP PEMBATALAN MEREK YANG TELAH DIDAFTARKAN (Studi Putusan Nomor 03/Pdt.Sus-MEREK/2015/PN Niaga Medan) - TIGOR MANGATUR LUHUT AMBARITA (PREMISE LAW JURNAL, 2019)
Dosen Pembimbing:1.  Prof. Dr. Saidin, SH, MHum2.  Dr. T. Keizerina Devi A, SH, CN, MHum3.  Dr. Jelly Leviza, SH, MHum Indonesia adheres to constitutive (first to file) system in brand registration as it is stipulated in Law No.20/2016 on Brand and declarative (first to use) system which is emphasized on first to use. One who first uses a brand will have the right to be the holder of that brand. The research problems are how about legal protection for the first registrant in the Indonesian legal system concerning brand revocation. how about evidence filed by the first registrant for revoking a brand which has been registered, and how about judge’s consideration in the Verdict No. 03/Pdt./Sus-Merek/2015/PN Niaga, Medan concerning a dispute between the first brad user and the first brand registrant, whether it has given legal certainty for both parties. The research used juridical normative method with prescriptive approach. It also used secondary data which were gathered by conducting library research and field research. Keywords: Revocation, Brand, has been Registered